Vaccination as an element of health security management - analysis of factors of patient attitudes towards COVID-19 preventive vaccinations based on the opinions of healthcare experts - Karczmarz, Sabina; Owczarczyk, Anna; Żuk, Paweł; Średziński, Leszek; Prusaczyk, Artur; Bogdan, Magdalena (Journal of Education, Health and Sport, 2024)
Background: Preventive vaccinations play a significant role in reducing the spread of infectious diseases. They mitigate the course of infectious diseases and limit the occurrence thereof. Thus, they allow maintaining the health security of citizens and are one of the activities that allow for effective population health management. However, even though vaccinations bring significant benefits to the population as a whole, the attitudes of individuals to them raise a number of controversies. Objective: The aim of the study was to analyze the characteristics and factors of patient attitudes towards COVID-19 preventive vaccinations based on the opinions of healthcare experts. The study was carried out in the framework of a project "The interdependence of lifestyle and attitudes towards COVID-19 preventive vaccinations", which finished in June 2023. Method: The research method was an in-depth telephone interview with experts who had previously studied the research problem and the results of quantitative research, and expressed individual opinions on the factors of patient attitudes towards COVID-19 vaccinations. The experts indicated various factors which, in their opinion, can influence patient willingness to be vaccinated against COVID-19. In the research process, four main factors were found: patient social environment and patient experience; patient knowledge and awareness, social impact (message of medical authorities and political decision makers), balance of benefits and risks. Results: The results obtained in the study and the conclusions drawn show the need for further, in-depth research in patient attitudes towards preventive vaccinations, not only COVID-19 vaccinations.